2012
DOI: 10.1007/s00429-012-0425-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of cannabinoid 1 receptor expression in the perikarya, and peripheral and spinal processes of primary sensory neurons

Abstract: The cannabinoid 1 (CB1) receptor is expressed by a sub-population of primary sensory neurons. However, data on the neurochemical identity of the CB1 receptor-expressing cells, and CB1 receptor expression by the peripheral and central terminals of these neurons are inconsistent and limited. We characterised CB1 receptor expression in dorsal root ganglia (DRG) and spinal cord at the lumbar 4–5 level, as well as in the urinary bladder and glabrous skin of the hindpaw. About 1/3 of DRG neurons exhibited immunoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 114 publications
(239 reference statements)
2
56
0
2
Order By: Relevance
“…Thanks to this presynaptic localization and to their ability to modulate calcium and potassium channel activities, CB 1 receptors have important functions in the regulation of neurotransmitter release in the brain and spinal cord 14 . Substantial levels of CB 1 expression are also found in nociceptive and non-nociceptive sensory neurons of the DRG 15,16,17,18 and trigeminal ganglion 19 , as well as in host-defense cells that make contact with those neurons (e.g., macrophages, mast cells and epidermal keratinocytes) 20,21 (Figure 2). Experimental interventions that evoke persistent hyperalgesia in animals are associated with profound changes in CB 1 expression in spinal and supraspinal structures of the CNS 22 .…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to this presynaptic localization and to their ability to modulate calcium and potassium channel activities, CB 1 receptors have important functions in the regulation of neurotransmitter release in the brain and spinal cord 14 . Substantial levels of CB 1 expression are also found in nociceptive and non-nociceptive sensory neurons of the DRG 15,16,17,18 and trigeminal ganglion 19 , as well as in host-defense cells that make contact with those neurons (e.g., macrophages, mast cells and epidermal keratinocytes) 20,21 (Figure 2). Experimental interventions that evoke persistent hyperalgesia in animals are associated with profound changes in CB 1 expression in spinal and supraspinal structures of the CNS 22 .…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 99%
“…Consistent with those results, in vivo pharmacological studies have demonstrated that cannabinoid agonists suppress nociceptive behaviors and CGRP release in rodents through a peripheral CB 1 -mediated mechanism 30,31,32,33 . The peripheral nature of these actions is strikingly illustrated by results obtained in mutant mice that specifically lack CB 1 in nociceptive neurons 17,18 . Compared to their wild-type littermates, these mice show decreased sensitivity to the analgesic effects exerted by local or systemic (but not intrathecal) administration of cannabinoid agents.…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 99%
“…These results correlate with the findings of others who have localized both CB with nerve fibres in the urothelium and detrusor. Veress et al [27] showed partial co-localization of CB1 with calcitonin gene-related peptide (CGRP, a marker for sensory nerves) in the muscular layer of rat bladders but there was no colocalisation in the urothelium. In our study we detected co-localisation of CB1 with the generic neuronal marker PGP 9.5 and ChAT in the mucosa, which supports the findings of the above study.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general agreement that CB 1 in this region is expressed by inhibitory interneurons co-expressing GABA, PKCγ and NO (Farquhar-Smith et al, 2000;Furuse et al, 2009;Nyilas et al, 2009;Pernia-Andrade et al, 2009). However, CB 1 expression in sensory afferents is still under discussion: while some studies report low levels or absence of CB 1 in substance P, CGRP, isolectin B4, β-subunit of cholera toxin and TRPV1 terminals (Ong and Mackie, 1999;Farquhar-Smith et al, 2000;Salio et al, 2002a,b;Furuse et al, 2009;Pernia-Andrade et al, 2009), others show CB 1 expression in primary afferents coming from dorsal root ganglion neurons projecting to the upper layers of the dorsal horn and in DRG-derived large myelinated fibers, that project to deeper layers of the spinal cord (Salio et al, 2002a,b;Bridges et al, 2003;Nyilas et al, 2009;Veress et al, 2013). Additionally, CB 1 in the intact spinal cord is expressed by glial cells: astrocytes (Salio et al, 2002a, b;Hegyi et al, 2009), microglia (Hegyi et al, 2009), oligodendrocytes (Garcia-Ovejero et al, 2009) and a subpopulation of ependymal cells (Garcia-Ovejero et al, 2013).…”
Section: The Endocannabinoid System In the Intact Spinal Cordmentioning
confidence: 99%